An effect-directed strategy for characterizing emerging chemicals in food contact materials made from paper and board. (August 2017) - Rosenmai, Anna Kjerstine; Bengtström, Linda; Taxvig, Camilla; Trier, Xenia; Petersen, Jens Højslev; Svingen, Terje; Binderup, Mona-Lise; Barbara Medea Alice, van Vugt-Lussenburg; Dybdahl, Marianne; Granby, Kit; Vinggaard, Anne Marie
Abstract: Food contact materials (FCM) are any type of item intended to come into contact with foods and thus represent a potential source for human exposure to chemicals. Regarding FCMs made of paper and board, information pertaining to their chemical constituents and the potential impacts on human health remains scarce, which hampers safety evaluation. We describe an effect-directed strategy to identify and characterize emerging chemicals in paper and board FCMs. Twenty FCMs were tested in eight reporter gene assays, including assays for the AR, ER, AhR, PPARγ, Nrf2 and p53, as well as mutagenicity. All FCMs exhibited activities in at least one assay. As proof-of-principle, FCM samples obtained from a sandwich wrapper and a pizza box were carried through a complete step-by-step multi-tiered approach. The pizza box exhibited ER activity, likely caused by the presence of bisphenol A, dibutyl phthalate, and benzylbutyl phthalate. The sandwich wrapper exhibited AR antagonism, likely caused by abietic acid and dehydroabietic acid. Migration studies confirmed that the active chemicals can transfer from FCMs to food simulants. In conclusion, we report an effect-directed strategy that can identify hazards posed by FCMs made from paper and board, including the identification of the chemical(s) responsible for the observed activity. Graphical abstract: Highlights: A strategy for an effect-directed analysis of food contact materials has been developed. Twenty food packaging materials were toxicologically profiled. Bisphenol A and phthalates were responsible for estrogenic activity of a pizza box. Abietic acid and dehydroabietic acid were responsible for androgen receptor antagonism in a sandwich wrapper. A tool for identifying emerging chemicals in food packaging has been developed.